2020
DOI: 10.1158/1078-0432.ccr-20-0341
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic High-density Lipoprotein Nanodiscs for Personalized Immunotherapy Against Gliomas

Abstract: ◥Purpose: Gliomas are brain tumors with dismal prognoses. The standard-of-care treatments for gliomas include surgical resection, radiation, and temozolomide administration; however, they have been ineffective in providing significant increases in median survival. Antigen-specific cancer vaccines and immune checkpoint blockade may provide promising immunotherapeutic approaches for gliomas.Experimental Design: We have developed immunotherapy delivery vehicles based on synthetic high-density lipoprotein (sHDL) l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…The reason for 40% of the mice treated with AGI-5198 to be tumor-free could be due the host's ability to mount a robust effector immune response, unlike the 60% of the mice which developed therapeutic resistance and succumbed due to tumor burden. The variability in the response to combination of radiotherapy, chemotherapy, and immunotherapy in brain tumor preclinical models has previously been demonstrated by several research groups (53)(54)(55)(56)(57). Mechanisms that contribute to treatment resistance are at present unknown and require further investigation (53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 94%
“…The reason for 40% of the mice treated with AGI-5198 to be tumor-free could be due the host's ability to mount a robust effector immune response, unlike the 60% of the mice which developed therapeutic resistance and succumbed due to tumor burden. The variability in the response to combination of radiotherapy, chemotherapy, and immunotherapy in brain tumor preclinical models has previously been demonstrated by several research groups (53)(54)(55)(56)(57). Mechanisms that contribute to treatment resistance are at present unknown and require further investigation (53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 94%
“…[4,12] In our previous work, we have shown that the nanodisc vaccine technology administered s.c. can efficiently drain to LNs and generate potent antigenspecific T cell responses. [5,19,20,43] In this work, we have utilized the nanodisc platform for therapeutic vaccination targeted against HPV16 E7 and shown elicitation of robust E7-specific CD8+ T cells, leading to the elimination of TC-1 tumors inoculated in various mucosal tissues, including intravaginal TC-1 model known for low T cell infiltration and aggressive features of HPV+ cervical cancer. [27,30,34] Importantly, in our head-to-head comparison studies, nanodisc vaccination induced comparable levels of antigen-specific CD8+ T cell responses as Listeria vectors ( Figures 6 and 7) but without any overt sign of toxicity or anti-vector immunity associated with live vector vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…Application of neoantigen-based cancer vaccines in murine tumor models, including melanoma [ 44 , 45 , 46 ], glioma [ 47 , 48 ], pancreatic carcinoma [ 49 ], and esophageal squamous cell carcinoma [ 50 ], has shown their potential in clinical translation. With encouraging results from preclinical research, the assessment of neoantigen-based cancer vaccines in clinical trials has been boosted significantly in recent years.…”
Section: Tumor-specific Antigensmentioning
confidence: 99%